GAMBARAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA SAAT PEMASANGAN INFUS PADA BALITA DI RUANGAN THERESIA RUMAH SAKIT SANTA ELISABETH BATAM KOTA TAHUN 2022 - Pomarida Simbolon; Jagentar P. Pane; Mestiana Br.Karo; Fitri Edika Parapat (Jurnal Cakrawala Ilmiah, 2024)
Anxiety is the body's response to threats from the external environment. Individuals who feel threatened by dangerous conditions, cause the brain to send commands to the body to release a compound called adrenaline. Adrenaline compounds cause a sense of alertness and also provide a form of strength for the body to respond to fight (attack) or flight (run). Infusion is a technique used to puncture a vein transcutaneously using a sharp, rigid stylet performed with a sterile technique such as an angeocatheter or with a needle attached to a syringe. Infusion is one way or part of treatment to introduce drugs or vitamins into the patient's body. ), family support is the participation of the family to provide assistance to one of the family members who need help both in terms of problem solving, providing security, and increasing self-esteem. The forms of family support are: emotional support, appreciation support, instrumental support, informational support. The purpose of this study was to identify the description of family support and the level of anxiety in the installation of intravenous infusion in toddlers in the Teresa Room, Santa Elisabeth Hospital, Batam City 2022. The research design used in this study was cross sectional. The population in this study were all under-five patients who were hospitalized in February 2022 with the inclusion criteria of parents who took care of their children during infusion and obtained a sample of 92 respondents. Sampling by purposive sampling. The results of the study obtained that the majority of family support was moderate support as many as 86 respondents (94%) and low support as many as 6 respondents (6%). The level of anxiety experienced by parents at the time of infusion for toddlers, the majority of which were severe anxiety as many as 56 respondents (68%) and mild anxiety as many as 26 respondents (32%), it can be said that, the majority of inpatients at Santa Elisabeth Hospital Batam City felt severe anxiety at the time of infusion in infants with moderate family support, therefore it is expected to maintain the quality of service and provide motivation and support for parents of patients who accompany toddlers in infusion